The study of the culturemes in translation ARABIC-SPANISH: Definitions and usages - Kissami Mbarki, Ahmed (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The study on culture is part of the research carried out by the Typological and Experimental Linguistics Research Group (GILTE) of the University of Granada. The objectives of our article consist of recapitulating various definitions on the subject and analyzing the impact that it could sustain in a given society as well as the speakers of it. The methodology responds to a descriptive analytical study putting on the technical table and fundamental questions related to cultures. The conclusions corroborated the initial starting point based on intercultural diversity and the variety of the intrinsic aspects of each culture.